2017
DOI: 10.1158/1940-6207.capr-16-0277
|View full text |Cite
|
Sign up to set email alerts
|

No Decreased Risk of Gastrointestinal Cancers in Users of Metformin in The Netherlands; A Time-Varying Analysis of Metformin Exposure

Abstract: Previous studies on metformin use and gastrointestinal (GI) cancer risk have yielded inconclusive results on metformin's chemoprotective effects. We aimed to evaluate GI cancer risk in users of metformin in The Netherlands using a time-varying approach in a large population-based database. A cohort study was performed using the NCR-PHARMO database. Patients using ≥1 non-insulin antidiabetic drug (NIAD) during 1998 to 2011 were included ( = 57,621). Exposure to NIADs was modeled time-varyingly. Cox regression a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 40 publications
0
32
0
Order By: Relevance
“…Analyzing data from observations of over 37,000 people treated with metformin, the results prove that the use of metformin does not reduce the risk of gastrointestinal cancer. Moreover, a higher risk of pancreatic cancer was observed in the group of patients using metformin with insulin and in women using metformin [25].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Analyzing data from observations of over 37,000 people treated with metformin, the results prove that the use of metformin does not reduce the risk of gastrointestinal cancer. Moreover, a higher risk of pancreatic cancer was observed in the group of patients using metformin with insulin and in women using metformin [25].…”
Section: Discussionmentioning
confidence: 98%
“…Metformin administered to diabetic patients in many scientific publications has been presented as a chemopreventive factor of cancer in the pancreas, colon or liver [23,24]. However, in recent years there have been studies showing that metformin does not reduce the risk of gastrointestinal cancers [25]. Analyzing data from observations of over 37,000 people treated with metformin, the results prove that the use of metformin does not reduce the risk of gastrointestinal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a study conducted in United Kingdom did not show a difference in GC incidence in patients receiving metformin compared to sulfonylureas[ 113 ]. Other reports also could not find any reduction in GC risk associated with metformin us[ 83 , 114 , 115 ]. Despite that, a meta-analysis showed a 21% reduction in the risk of GC with the use of metformin, in Asians the benefit was more prominent than in Westerners[ 116 ].…”
Section: Metformin Studies In Digestive System Malignanciesmentioning
confidence: 89%
“…By contrast, studies which were deemed incompatible and therefore not included in these meta-analyses indicated that metformin use was not associated with a reduced risk of developing GI cancer. A population-based cohort study in the Netherlands revealed that metformin use was not associated with a decreased risk of stomach, liver, pancreatic, and colorectal cancers (HR: 0.97, 95% CI: 0.82–1.15) ( 14 ) and also failed to detect changes in the risk of cancer according to an increase in the cumulative dose of metformin. This study included 35,654 subjects (62.4%) with at least 1 year of antidiabetic medication-free follow-up and 21,460 subjects (37.6%) with prevalent use of antidiabetic medications.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, other studies that were not included in these meta-analyses reported conflicting results. de Jong et al ( 14 ) reported that metformin use was not associated with a decreased risk of any type of GI cancer, whereas Bodmer et al ( 15 ) reported that metformin use was not associated with a decreased risk of colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%